Fertilitas dan Daya Tetas Itik Lokal di Desa Bulukarto, Kabupaten Pringsewu - Cintia Agustin Patria; Maria Herawati (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2018)
This research aims to find out the production of hatching eggs from local ducks in Bulukarto Village, Pringsewu Regency based on fertility and hatchability value. The percentage of fertility were 83,97% higher than other research and hatchability value were 81,12%. Keywords: hatchability, fertility, duck, eggs